Efektifitas Penggunaan ATS (Australasian Triage Scale) Modifikasi Terhadap Response Time Perawat Di Instalasi Gawat Darurat - Sofiyanti Normalinda Banoet; Harmayetty Harmayetty; Laily Hidayati (Universitas Airlangga, 2019)
Introduction: Triage is the process of sorting patients according to their severity. However, the phenomena that occur in the emergency room of some hospitals are different, triage is not carried out according to the standards. This is due to many factors, one of which is the triage model used. The purpose of this study was to look at the relationship between the use of Standard Operations Procedure for admitting new patients using ATS triage which was modified with the speed of response of nurses in the Emergency Installation. Method: This study used a correlative analytical design with a case study approach. The total population is 31 people and a sample of 28 people was obtained through inclusion and exclusion criteria. The independent variable in this study was the use of ATS (Australasian Triage Scale) and the dependent variable in this study is the nurse's Response Time. Data obtained by means of sample observation and analyzed using the Spearman correlation test rho. Results: There was no association between the use of ATS (Australasian Triage Scale) modification and the response time of nurses in the morning shift (p = 0.720), day shift (p = 0.866) and night shift (p = 0.173).Discussion: From the results of the study there was no relationship between the use of ATS (Australasian Triage Scale) and the response time of nurses in the morning, afternoon and night shift. The use of ATS modification and the response time of nurses that are appropriate and fast are found in morning service. This is caused by several factors both from the nurses themselves and from the hospital. Most nurses do not get training in Triage and this affects nurses' skills in sorting patients.